Role of EU in Sustainable Fashion Development - Geršlová, Barbora (2018)
This research aims to analyse the current state of fashion and assess its negative impact on environmental and social issues, while investigating the role of EU in the transformation of the fashion industry into a sustainable business. It attempts to quantify the negative effects and to suggest improvements from EU perspective in order to avoid reaching the environmental critical point caused by the fashion industry.